Enhancing governance and strengthening advocacy for policy change of large Collective Impact initiatives. (22nd February 2019) - Michaud‐Létourneau, Isabelle; Gayard, Marion; Mathisen, Roger; Phan, Linh Thi Hong; Weissman, Amy; Pelletier, David Louis
Abstract: Nutrition issues are increasingly being addressed through global partnerships and multi‐sectoral initiatives. Ensuring effective governance of these initiatives is instrumental for achieving large‐scale impact. The Collective Impact (CI) approach is an insightful framework that can be used to guide and assess the effectiveness of this governance. Despite the utility and widespread use of this approach, two gaps are identified: a limited understanding of the implications of expansion for an initiative operating under the conditions of CI and a lack of attention to advocacy for policy change in CI initiatives. In this paper, a case study was undertaken in which the CI lens was applied to the advocacy efforts of Alive & Thrive (A&T), UNICEF and partners. The initiative expanded into a regional movement and achieved meaningful policy changes in infant and young child feeding policies in seven countries in Southeast Asia. These efforts are examined in order to address the two gaps identified in the CI approach. The objectives of the paper are (a) to examine the governance of this initiative and the process of expansion from a national to a regional, multilayered initiative, with attention to challenges, adaptations, and key elements, and (b) to compare advocacy in the A&T–UNICEF initiative and in typical CI initiatives and gain insight into how the practice of advocacy for policy change can be strengthened in CI initiatives.